2021
DOI: 10.1002/ece3.7836
|View full text |Cite
|
Sign up to set email alerts
|

Excluding spatial sampling bias does not eliminate oversplitting in DNA‐based species delimitation analyses

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 117 publications
2
11
0
Order By: Relevance
“…The correlation between divergent genital morphology and evolutionary entities was widely confirmed by integrative taxonomy studies (Ahrens & Ribera, 2009;Eberle et al, 2016), including even genomic data (Dietz et al, 2021). The here observed low congruence of MOTUs with morphospecies (match ratio: 0.57-0.67) was not unexpected since previous studies on tropical Sericini have showed similarly low match ratios Dalstein et al, 2019;Lukic et al, 2021). Some of them were subject to strong variation (between 0.14 and 1) depending on the different selected subclades being analyzed .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The correlation between divergent genital morphology and evolutionary entities was widely confirmed by integrative taxonomy studies (Ahrens & Ribera, 2009;Eberle et al, 2016), including even genomic data (Dietz et al, 2021). The here observed low congruence of MOTUs with morphospecies (match ratio: 0.57-0.67) was not unexpected since previous studies on tropical Sericini have showed similarly low match ratios Dalstein et al, 2019;Lukic et al, 2021). Some of them were subject to strong variation (between 0.14 and 1) depending on the different selected subclades being analyzed .…”
Section: Discussionsupporting
confidence: 81%
“…While results of COI barcoding have been so far mainly compared with morphospecies entities, the congruence of the outcome of different DNA‐based species delimitations has only rarely been analyzed in detail. Outcomes have often been characterized as “different” without quantifying the difference (Ahrens et al, 2016; Dalstein et al, 2019; Lukic et al, 2021). These differences are explored here in detail, exemplified by a case study of Sri Lankan Sericini chafers.…”
Section: Introductionmentioning
confidence: 99%
“…All these results emphasize the importance of assessing species boundaries within an integrative framework, in which not only molecular data but also morphological, life history and ecological information are considered (e.g., Lukic et al, 2021).…”
Section: Phlyctinus Diversity and Phylogenetic Relationshipsmentioning
confidence: 84%
“…Considering disagreements between morphospecies registered in the sequence database and the estimated ESUs, anatomical morphology can help us to evaluate the species diversity with the species delimitation results ( Lukic et al, 2021 ). Five ESUs in our sites can be largely distinguished into four morphological patterns ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). In this study, we conservatively treat ESU 28 and ESU 29 as a single species because there are no morphological differences in genitalia or external appearance, and some species delimitation methods are known to oversplit ( Lukic et al, 2021 ). ESU 30 has also very similar external morphology to that of ESU 28 and ESU 29, but pattern of genitalia such as the digitiform gland was clearly different ( Fig.…”
Section: Discussionmentioning
confidence: 99%